Menstrual Characteristics among Female Students in University of Port Harcourt and It’s Risk Factors - , Ibinabo Fubara Bob-Manuel, Comfort Eke (Archives of Current Research International, 2023)
Background: For women of reproductive age, menstruation is a common and natural occurrence. This is characterised by bleeding from the endometrium brought on by the removal of the functional layer of the endometrium of the uterus. Women from all over the world are affected by menstrual-related disorders, which are increasingly one of the main triggers for gynaecological appointments. Aim: The purpose of the current study is to identify the menstrual characteristics, menstrual difficulties, and risk factors among female students at the University of Port Harcourt. Materials and Methods: A questionnaire were distributed to one hundred and forty (140) female undergraduate students each at the University of Port Harcourt for this study, which was done as a cross-sectional research study in 2022. Results: Due to a variety of factors that contribute to the irregularity of menstruation patterns, the investigation revealed that menstrual problems are common among female students. Dysmenorrhea is reported to be the most frequent (47.1%) and common menstrual characteristics or symptom among female students. Other common menstrual symptom found in this study were acne, body pains, tender/swollen breasts, fatigue, fever, bloating, nausea, diarrhoea and frequent urination which is similar to other studies. Conclusion: The result of this study would help enlighten females and physicians on the menstrual characteristics, some common disorders among female students, and the risk factors associated to the menstrual characteristics.